2020
DOI: 10.1177/0003134820964496
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a Novel Clinical Criteria to Predict Candidacy for Aortic Occlusion: An Aortic Occlusion for Resuscitation in Trauma and Acute Care Surgery Study

Abstract: For trauma patients with noncompressible truncal hemorrhage (NCTH), aortic occlusion (AO) is attempted with either resuscitative thoracotomy (RT) or the resuscitative endovascular balloon occlusion of the aorta (REBOA). However, it is often challenging to identify the group of patients who would benefit from AO procedures. We hypothesized that patients who met simple clinical criteria would have better outcomes following AO procedures. This is a retrospective cohort study using the Aortic Occlusion for Resusci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…Reserving REBOA only for very severe PAS cases, selected with presurgical evaluation of the invasion topography and intraoperative staging (parametrial involvement and viability of safe vesicouterine dissection), is a valid strategy when carried out by experienced groups who have additional technical resources to identify these patients and control unexpected intraoperative bleeding 8,12 . Our observation coincides with experiences in trauma patients, in which the appropriate REBOA candidates selection defines the effectiveness of the technique and the complications frequency 28 . Our experience reflects the benefits of interdisciplinary work and the application of learnings on trauma field, to the obstetric population.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Reserving REBOA only for very severe PAS cases, selected with presurgical evaluation of the invasion topography and intraoperative staging (parametrial involvement and viability of safe vesicouterine dissection), is a valid strategy when carried out by experienced groups who have additional technical resources to identify these patients and control unexpected intraoperative bleeding 8,12 . Our observation coincides with experiences in trauma patients, in which the appropriate REBOA candidates selection defines the effectiveness of the technique and the complications frequency 28 . Our experience reflects the benefits of interdisciplinary work and the application of learnings on trauma field, to the obstetric population.…”
Section: Discussionsupporting
confidence: 72%
“…8,12 Our observation coincides with experiences in trauma patients, in which the appropriate REBOA candidates selection defines the effectiveness of the technique and the complications frequency. 28 Our experience reflects the benefits of interdisciplinary work and the application of learnings on trauma field, to the obstetric population.…”
Section: Discussionmentioning
confidence: 84%
“…Future directions may also include investigating the utility of incorporating Glasgow Coma Scale (GCS) score into REBOA patient selection decision-making, as a recent Aortic Occlusion for Resuscitation in Trauma and Acute Care Surgery (AORTA) registry study reported that GCS score ≥9 and SBP <90 were useful predictors of success of aortic occlusion. 23 Alternatively, in the context of a poor GCS score due to penetrating TBI, REBOA may be used as a less invasive means of aortic occlusion for the purpose of defining survivability for organ donation.…”
Section: Discussionmentioning
confidence: 99%
“…The criteria for REBOA decision making, timing, and identification of those who could benefit, whether prehospital or in-hospital, remain disputed. 15,[34][35][36] To give guidance to a widely supported protocol, we tried to narrow indications by combining trauma mechanism, physiological thresholds, response to fluid therapy and estimated transportation times. Earlier, SBP thresholds of 60 mm Hg to 70 mm Hg in penetrating and blunt trauma patients have been proposed as cutoff for aortic occlusion.…”
Section: Discussionmentioning
confidence: 99%